Information Literacy Instruction in Business Schools: Factors Affecting the Adoption of Online Library Resources by Business Students - Booker, Lorne D. (My University, 2011)
The overall goal of this dissertation is to predict and explain how information literacy instruction (ILI) influences the adoption of online library resources (OLRs) by business students. This dissertation has two other important goals. First, this dissertation aims to assess the efficacy of active ILI and passive ILI. Second, this dissertation seeks to examine the role that OLR self-efficacy and OLR anxiety play in influencing ILI learning outcomes and the adoption of OLRs.
To achieve these goals, a theoretical model was developed that integrates research on ILI outcomes and technology adoption. To test this model, a web-based survey was developed and administered to 337 business students at McMaster University.
This dissertation makes several important contributions to theory. First, the findings from the analysis of the structural equation model confirm that the Technology Acceptance Model is an appropriate tool for studying the adoption of OLRs. Second, the findings indicate that amount of ILI is not a significant predictor of the adoption of OLRs. Third, though the amount of ILI was not found to be a predictor of OLR self-efficacy or OLR anxiety in the quantitative analysis, results from the qualitative analysis suggest that ILI increases self-efficacy and reduces anxiety. Fourth, the findings suggest that OLR self-efficacy and OLR anxiety are significant determinants of the adoption of OLRs where OLR self-efficacy was the strongest determinant of the adoption of OLRs. Last, consistent with Bandura’s social cognitive theory, OLR self-efficacy and OLR anxiety were found to be significantly negatively correlated; a partial mediation effect of OLR anxiety on the relationship between OLR self-efficacy and the perceived ease of use of OLRs was supported.
This dissertation makes a contribution to practice by revealing that instructors should focus on delivering higher quality ILI rather than higher amounts of ILI. In particular, training interventions should be designed to promote OLR self-efficacy among business students, especially among students who have received the least amount of ILI.
Keywords: Information Literacy; Information Literacy Instruction; Online Library Resources; Online Library Resource Self-Efficacy; Online Library Resource Anxiety; Technology Adoption; Technology Acceptance Model; Active Instruction; Passive Instruction; Electronic Library Anxiety; Library and Information Science; Management Information Systems; Library and Information Science